2019
DOI: 10.3390/ijms20246347
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of the S-acyltransferase Gene, PbPAT14, Confers the Dwarf Yellowing Phenotype in First Generation Pear by ABA Accumulation

Abstract: The development of dwarf fruit trees with smaller and compact characteristics leads to significantly increased fruit production, which is a major objective of pear (Pyrus bretschneideri) breeding. We identified the S-acylation activity of PbPAT14, an S-acyltransferase gene related to plant development, using a yeast (Saccharomyces cerevisiae) complementation assay, and also PbPAT14 could rescue the growth defect of the Arabidopsis mutant atpat14. We further studied the function of PbPAT14 by designing three gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Previous studies suggested that S-acyltransferases play an important role in regulating plant architecture in plants [ 23 , 24 , 25 , 26 ]. Therefore, we focused on GRMZM2G010011 to further validate its function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that S-acyltransferases play an important role in regulating plant architecture in plants [ 23 , 24 , 25 , 26 ]. Therefore, we focused on GRMZM2G010011 to further validate its function.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, OsPAT15 regulates plant architecture by altering the tiller in rice [ 24 ], and overexpression of OsPAT15 results in increased branch and seed yield in Brassica napus [ 37 ]. Knockout lines of PbPAT14 exhibited the dwarf yellowing phenotype, and the function of PbPAT14 was related to the ABA pathway [ 25 ]. In addition, Hemsley et al (2005) reported an S-acyltransferase gene in Arabidopsis , Tip Growth Defective 1 ( TIP1 ) /PAT24 , which exhibits impairment in root hair elongation and defective growth of pollen tubes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This leds to decrease photosynthesis by promoting ABA-mediated chlorophyll degradation ( Asad et al, 2019 ) and reducing carbon dioxide in-take and therefore retards apple tree growth. Similarly, the pear trees which accumulated with ABA also show dwarfing phenotype after knockout of PbPAT14 ( Pang et al, 2019 ). The similar phenomenon of dwarfing phenotype due to ABA accumulation was also found in Gerbera hybrida and Arabidopsis thaliana ( Yang, Worley & Udvardi, 2015 ; Ren et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…ABA level is induced by drought stress. Its metabolic pathway has been well studied ( Shu et al, 2016 ; Ren et al, 2018 ; Pang et al, 2019 ). Shi et al (2021) reported that the drought-induced OsAAO3 regulates rice growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…In the dwarf pear ( Pyrus bretschneideri ), the tree achieved enhanced yield; the loss-of-function mutant of the PbPAT14 gene was generated by the CRISPR/Cas9 system. Sequence analysis revealed that out of 22 dwarf yellow lines, six were homozygous mutants and had an elevated level of endogenous abscisic acid (ABA) [ 152 ].…”
Section: Genome Editing In Precision Breedingmentioning
confidence: 99%